Genre analysis of job application letters in Malaysia - Paramasivam, Shamala; Rahim, Muhamad Izzat (English Language Education Publishing, 2016)
A job application letter is the first business document that an applicant encounters in workplace correspondence. Despite its importance, however, the genre is understudied. The present study was conducted to examine the schematic structure: move patterns and communicative purposes of moves in job application letters written in English by a group of applicants, so as to gain an understanding of their lacks and needs when writing the letter. Discourse and genre analysis make up the research design. Genre theory and the theory of cooperation in communication were used to guide the study; Bhatia’s (1993) framework for moves in job letters and Grice’s (1975) model for cooperation in communication were used as the frameworks for analysis. Data constituted authentic letters of application to a Malaysian small to medium enterprise. The findings show that Malaysian fresh graduates use a 5-move structure and have, to a certain extent, grasped the basic format of the job application letter. Nonetheless, they still have problems in writing an effective letter. The problematic moves are Essential Detailing of Candidature, Indicating Value of Candidature and Offering Incentives. The moves lack clarity and textualisation in terms of quantity and quality of semantic content and linguistic input. As a result, self-appraisal is weak because applicants are unable to promote and present their individuality as useful and valuable persons to the company with unique achievements, abilities and skills. The study gives insights into the use of multiple theories and analytic methods for doing a genre analysis and the findings are useful for teaching and learning letter writing in the contexts of ESL, EAP and ESP.